THE REPARATIVE EFFECT OF TRUTH SEEKING IN TRANSITIONAL JUSTICE. Issue 1 (29th January 2015) - Unknown
Abstract: The benefits of a 'holistic' approach to transitional justice are enhanced by considering how synergies between different transitional mechanisms may be optimized. Drawing upon multiple examples, this article explores the potential contribution of truth seeking to reparation efforts at a normative, institutional and operational level. The article emphasizes the importance of an awareness of the reparative potential of truth seeking on the part of those implicated in its design and implementation, as well as an appreciation of the influence of contextual factors on a delicate process. It cannot be conceived of simply as a technocratic exercise, but as an inherent part of empowering victims.